NEED ANALYSIS ON ENGLISH FOR ISLAMIC ECONOMICS DEPARTMENT STUDENTS AT UIN ALAUDDIN MAKASSAR - Nurhasana, Andi Ratu Nurhazana Ratu; Nurasik, Nurasik; Asmawati, Andi (English Language Teaching for EFL Learners Journal, 2021)
This research aims to find out the present situation needs of English and the target situation needs of English for Islamic Economics department students at UIN Alauddin Makassar. The research design used in this study was survey method, the data were obtained from the students’ need. This study involved 59 respondents which consists of 52 students of the 2nd semester batch 2019, 2 lecturers, 1 expert and 4 graduates, from Islamic Economics department at UIN Alauddin Makassar. In collecting the data, the instrument was used the questionnaire for students, graduates, lecturers, expert, and used interview. The collection of the data was done by distributing the questionnaires to the participants to identify the students’ need in Islamic Economics and interview guideline to find additional data. The researcher involved four activities; observing English teaching and learning process, giving questionnaires, analyzing and describing the obtained data, and calculating the percentage of questionnaires. The findings revealed of this research showed the students present and target situation needs. First, Present situation analysis consisted of level ability, English skill and component, topic, then problem in learning English. Level ability needed by the students was reading. English skills and component needed most by the students was grammar. The topics that students needed was alms. Meanwhile, most of the problem that students have based on questionnaires was the students lack of learning strategies in English. Second, target situation analysis consisted of learning preference and learning purposes. Learning preference that was needed the most by students was using film or video in learning process. Furthermore, learning purposes that was mostly chosen by students was future career in learning English.